Intraosseous lipoma of the calcaneum - Khujat, Rohan; M. Khaladkar, Sanjay; Kharat, Amit; Raj, Raunak; Doshi, Foram; Gandage, S.G (International Journal of Medical Research and Review, 2016)
Calcaneal Intraosseous lipoma is a very rare lesion usually benign tumor, which constitutes not more than 2% of bone tumors. On plain radiographs, an intraosseous lipoma is usually seen as benign-appearing osteolytic bone lesion with well-defined margins and calcified/ossified dense matrix. Plain radiographs alone cannot establish the diagnosis of intraosseous lipoma as it imitates several other benign and malignant bone lesions. Intraosseous lipoma contains calcified necrotic fat with mature adipose tissue and characteristically induces expansion/remodeling of the affected bone.